Management of bilateral microspherophakia with secondary angle closure glaucoma - Malik, K PS; Goel, R; Jain, K; Nagpal, S; Singh, S (Nepalese Journal of Ophthalmology, 2015)
Background: Microspherophakia is characterized by lenticular myopia, late development of lens dislocation, shallow anterior chamber and angle-closure glaucoma. If it is associated with angle closure glaucoma, the management can be challenging.Objective: To report the management of a case of bilateral secondary angle closure glaucoma with isolated microspherophakia and right subluxated lens in a middle aged lady. Case: A 47-year-old female presented with bilateral secondary angle closure glaucoma with isolated microspherophakia, right subluxated lens and left operated trabeculectomy. The patient`s best corrected log mar visual acuity improved from 1.0 to 0.2 and intraocular pressure (IOP) decreased from 24.9mm of Hg to lower teens following lensectomy with scleral ¿xation of posterior chamber intraocular lens in the right eye. The left eye IOP remained in mid teens without medication in two year follow up. Conclusion: This case demonstrates that microspherophakia should be ruled out even in middle aged patients presenting as angle closure glaucoma. The possibility of thickened cornea must be kept in mind requiring an IOP correction. Lensectomy with scleral ¿xation of posterior chamber IOL provides a satisfactory recovery of visual acuity and IOP control. Though in this patient, the lens was held in position by posterior synechiae in the left eye, future stability of zonules needs to be monitored.